MANAJEMEN KEPALA MADRASAH DALAM IMPLEMENTASI KURIKULUM 2013 DI MADRASAH ALIYAH NEGERI 1 KOLAKA KABUPATEN KOLAKA - Ansani Ansani; Aziz Baking (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
Achievement of success in an organization depands of manager who runs the operational functions, such as planning, organizing, actuating, and controlling the people and others resource, including managing the curriculum. Headmaster as leader of educational institutions have big rolesfor creating conducive atmosphere that exist in work environment. The condusive atmosphere is most important factor for creating an outstanding teachers. This research is the kind of qualitative research. Data obtained from the results of the interviews, observation, and documentation in MAN 1 Kolaka. Technique of data analysis used are reduction of data, data analysis and presentation of conclusions. Test the validity of the data using triangulation, observation, diligence, analysis qualitative with the associate member and check. Teachers as educators have very important role to the progress of the Indonesian nation. Teachers as well as of the critical success factors (curriculum success). Especially teachers is the soul of the Madrasah or school. Duties and responsibilitiesof headmaster in the curriculum implementation 2013 could include activities implementation and managerial functions, including as planning, organizing, actuatingand controlling. In order for duties impelemtation and for that responsibilities, headmaster has required to master several competencies and managerial ability.